Finansial development, real sector and economic growth: Finansial development, real sector and economic growth - Rashidov, Jamshid (Архив научных исследований, 2021)
This article reaveled colloboration of real sector and finance sector of economy, supporting measures for both sectors and its influense on the development and growth of economy.